(Flavour Fixation of Shallot and Soup Leek) - Sait, Salya; Hawani Lubis, Enny (Balai Besar Industri Agro, 1993)
The flavours of shallot (Allium cepa linn)and soup leek (A.fistulosum.linn)were separated from their natural sources using solvent extraction technique as wellas juice expression.In the forms of viscous extract liquid and juice concentrate, the flavours were than fixed using the fixation formula US patent 3,619,212; November 9,1971.The stability of aroma and the resistance to microorganisms during storage, and the aroma preference of all fixatives produced were also studied.The result showed that relatively the best stability of aroma was proccessed by the fixatives derived from the extract obtained via the solvent extraction using ethanol 1:1 the resistance to microorganisms of all fixatives was excellent,and the result of sensory eavaluation indicated that the aroma of fixatives derived from the juice concentrate were prefered over thosefrom the ethanol extract.